The cultural values of the azfya emirate in the countries of the Maghreb From the year (646-747 AH / 1248-1345 AD) The Prophet's birthday as a model (Journal of the College of Basic Education, 2022)
Al- Azfi Emirate got a great fame in Morocco and Andalus. It had an excellent reputation among the people of Ceuta, Tangier and their villages, as well as gratify al- Muwahids Caliphs; that’s because they ruled justly, interested in the well fare of subjects, protected their shore cities, erected the country and planted the land, so peace and well far overwhelmed their land. In this paper the scholar wanted to emerge another important think in the life of this Emirate which is the civilized side and the values the society inspired through reviving the birth of prophet Mohammed (may God bless him) calibration which by that they were on the contrary from Jews and Christians, through reciting Quran, reviving his biography, complementing him by poems as well as reviving his dispositions in social solidarity, family bounding, as they are represent social sound values. That reviving of the prophet’s Mohammed birth met an agreement from some jurists and refused from others, as the said that it is heresy; but the Azfis’ insisting on such calibration made all the country of Morocco and Granada celebrate annually in it to let the bless of such great birth overwhelm the country. All thanks for the Azfi’s princes by their reviving to those Mohammadi human values and principals